XIX Balcanicum conference. Borders in the Balkans and Central Europe and the practice of everyday life, 23–24 October 2020 - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2020)
Report from the XIX "Balcanicum" Borders in the Balkans and Central Europe and the practice of everyday life conference, Poznań, 23-24 October 2020.